Analytic Solution of Electromagnetic Transient in a Polyphase Transmission Systems - Jingke, Chen (Philippine Engineering Journal; Vol 8 No 2 (1987), 2021)
For the first time, this paper gives analytic solutions in the time-domain and natural frequencies of nonsymmetrical exciting system after solving the matrix partial differential equations which describe electromagnetic behaviour on polyphase lossy-transmission lines, the frequency-dependent parameters of which are considered, by using classical method strictly. It is beneficial to the analysis of principle of protections based on travelling-wave and to the proposition of new criteria for protection. To verify the result, an example is taken which is offered by G.W Swiftn [1] and solved by Bergeron’s method [2]. In the paper, several concepts are given. At the appendix, the correctness of solutions are proved mathematically.